Implementasi System Real Time untuk Monitoring Pencahayaan Suhu dan Kelembaban pada Tanaman Stroberi - Agung Leona Suparlin; Sabriansyah Rizkiqa Akbar; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Fragaria is a genus of flowering plants in family rose, rosaceae, known in general in the name of strawberries for its fruit that can be consumed.But, there are several factors that it should be noted that plant strawberries can grow well the limit values for lighting, temperature, and humidity land.If factors are not achieved, but the growth of plants strawberries will not maximum or plant will dry up and died. Based on these problems, required a system that can afford to run monitoring based on lighting, temperatures and moisture land in plants strawberries. In this research there are 3 sensors that is the censor light LDR, sensors temperature LM35, and sensors moisture land SEN0114 connected with microcontroller arduino mega.The output of the system displayed using LCD and the warning lights LED RGB. In arduino mega embedded RTOS that served as scheduling task on the system. The RTOS used is already provided in the Arduino Mega library ie FreeRTOS. From the test results, the system can be determine the range of conditions in monitoring the strawberries accuracy reaches 100 %. Scheduling tasks performed in accordance with the priorities made. The average system execution time using RTOS is 88,6ms, while the system without RTOS is 76,9ms. System with RTOS takes longer time, because in system there is take-and-give semaphore function which need execution time for Â± 1,64ms.